2020
DOI: 10.1177/2158244019898264
|View full text |Cite
|
Sign up to set email alerts
|

The Interplay of Leadership Styles, Innovative Work Behavior, Organizational Culture, and Organizational Citizenship Behavior

Abstract: Leadership stains affect the follower’s performances regarding innovative work behavior, and a gap is found in leadership research in higher education, specifically in Pakistan. The basic purpose of this research is to point out the effect of leadership styles on innovative work behavior under the mediating and moderating roles of organizational culture and organizational citizenship behavior among the Head of the Departments (HODs) in higher education institutions (HEIs). A survey method has been carried out … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
148
1
18

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 193 publications
(264 citation statements)
references
References 52 publications
(86 reference statements)
13
148
1
18
Order By: Relevance
“…The toxic/abusive leadership is found to be dishonest, disrespectful, withholding information and so forth (De Clercq et al, 2020;Khan et al, 2020;Kim, 2020) that are the intangible or non-physical behaviors. Keeping a focus on banks, Asrar-Ul-Haq and Kuchinke (2016) revealed leadership styles affecting bank employee's performance especially laissez-faire leadership style having an adverse effect on the performance outcomes effectiveness, satisfaction, and extra effort.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The toxic/abusive leadership is found to be dishonest, disrespectful, withholding information and so forth (De Clercq et al, 2020;Khan et al, 2020;Kim, 2020) that are the intangible or non-physical behaviors. Keeping a focus on banks, Asrar-Ul-Haq and Kuchinke (2016) revealed leadership styles affecting bank employee's performance especially laissez-faire leadership style having an adverse effect on the performance outcomes effectiveness, satisfaction, and extra effort.…”
Section: Discussionmentioning
confidence: 99%
“…Supervisors practicing inequity dismantle the stability of the association between supervisors and subordinates. Disturbing affection, anxiety, and other uncooperative conditions trigger negative perspectives and behaviors (Khan et al, 2020), such as low job satisfaction and ultimately desire to leave the organization (De Clercq et al, 2020).…”
Section: Abusive Leadership and Organizational Commitmentmentioning
confidence: 99%
See 2 more Smart Citations
“…The findings of Eissa (2019) also shown that the employee with OCB characteristics will less likely to deviate from their jobs and be more associated with their job in the organization despite their other negative influencing factors. Furthermore, Khan (2020) examined that OCB is of vital importance that seems to dominate over other behaviors in an employee without any involvement of any rewards; even the employee considers his duty of being loyal and committed to the organization.…”
Section: Introductionmentioning
confidence: 99%